Emotion regulation beyond executive and attention difficulties: impact on daily life impairments in community adolescents - Elena Poznyak; Martin Debbané (Child and Adolescent Psychiatry and Mental Health)
Abstract Background It is becoming widely recognized that emotion regulation difficulties are an essential feature present along the continuum from subclinical to clinical Attention Deficit/Hyperactivity Disorder (ADHD). Yet, it remains unclear whether and how specific processes related to emotion regulation contribute to daily life impairments, across different domains of functioning. The aim of this cross-sectional study in community adolescents was to investigate whether three processes commonly implicated in adaptive emotion regulation—emotion recognition, emotion reactivity and use of cognitive emotion regulation strategies—uniquely contribute to adolescent-rated functional impairment, above and beyond the effects of age and gender, ADHD symptoms, and individual differences in verbal ability and executive functions. Methods 161 adolescents from the general population (mean age = 15.57; SD = 1.61) completed the Weiss Functional Impairment Scale, the Emotion Reactivity Scale, the Cognitive Emotion Regulation Questionnaire and the Geneva Emotion Recognition Test. Hierarchical regression analysis examined the unique contributions of candidate predictors to impairment scores. Results Total impairment scores were best predicted by older age, inattention symptoms, higher emotion reactivity, and higher use of maladaptive cognitive emotion regulation strategies. Emotion regulation processes were associated with interpersonal difficulties and self-concept impairments, whereas inattention symptoms were associated with school and life skills impairments. Conclusions This study stresses that emotion reactivity and maladaptive cognitive emotion regulation represent major sources of perceived social and emotional difficulties in community adolescents. Our results also support the continuum hypothesis of attention difficulties, where emotion regulation abilities may at least partially explain the association between ADHD symptoms and social impairments. Together, these findings highlight the vital importance of targeting emotion regulation in psychotherapeutic interventions aiming to improve socio-emotional outcomes in adolescents.